(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This study analyzes the causes and consequences of regional socio-economic disparities between countries. It highlights how inequalities are reflected in income levels, education, and health indicators. The experiences of Germany, China, and South Korea were studied to understand policies aimed at reducing regional disparities. The study concluded that reducing regional disparities is crucial for sustainable economic growth and social stability.